PEDAGOGICAL TESTING AS A MEANS OF EDUCATIONAL MONITORING: MANAGEMENT ASPECT (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem concerning existing possibilities of pedagogical testing while forming monitoring system of education establishments on managers' level.
Keywords: pedagogical testing; monitoring; management; control in education establishments